Renoprotection of Microcystin-RR in Unilateral Ureteral Obstruction-Induced Renal Fibrosis: Targeting the PKM2-HIF-1α Pathway - Ren, Yan; Wang, Jie; Guo, Wenwen; Chen, Jingwen; Wu, Xin; Gu, Shubo; Xu, Lizhi; Wu, Zhiwei; Wang, Yaping (Frontiers in Pharmacology, 2022)
Renal fibrosis is a pathological characteristic of the endpoint of chronic kidney disease (CKD), which remains a major public health problem. None of the current therapies is effective to stop kidney fibrosis progression. In the light of our novel detection on a potential antifibrosis of microcystins (MCs), we investigate the renoprotection effect of MCs with UUO-induced renal fibrosis. The treatment of MCs was initiated in model animals in advance of UUO operation. With determining that the anti-fibrotic effect of MCs was independent of its toxicity, we focus study on the renoprotection of microcystin-RR (MC-RR), a lower toxic congener of MCs, in UUO mice and the cell models in vitro. The co-immunoprecipitation assay and recombination plasmid transfection was used in the investigation on the mechanism of anti-fibrosis of MC-RR. The data show that MC-RR substantially exerts an effect on renoprotection with suppression of the expression of TGF-β1/Smad signaling molecules, and a blockage in epithelial dedifferentiation and myofibroblasts activation in UUO model animals. MC-RR shows a binding directly to pyruvate kinase M2 (PKM2), downregulates PKM2-HIF-1α signaling, restores the inhibited expression of MMP-7 and MMP-13, and reduces the upregulated expression of MMP-9 in UUO renal tissues. The current study demonstrates a novel effect of MC-RR on renoprotection in kidney damage, which could be conducted in therapeutics for chronic kidney disease.